2023
DOI: 10.3389/fmicb.2022.1096186
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of anaerobic thermophiles and putative anaerobic nickel-dependent carbon monoxide-oxidizing thermophiles in mesothermal soils and sediments

Abstract: Even though thermophiles are best known from geothermal and other heated systems, numerous studies have demonstrated that they occur ubiquitously in mesothermal and permanently cold soils and sediments. Cultivation based studies of the latter have revealed that the thermophiles within them are mostly spore-forming members of the Firmicutes. Since the geographic distribution of spores is presumably unconstrained by transport through the atmosphere, similar communities (composition and diversity) of thermophiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…It is important to note that the pioneering work [ 19 ] and some subsequent studies [ 43 , 45 ] included samples from soils exposed to hot temperatures and others from cold environments. Additional studies have shown significant roles of thermophiles at higher latitudes [ 16 , 17 , 49 , 50 , 51 , 52 ], corroborating that soil thermophiles can also show significant environmental activity in relatively cold climate zones.…”
Section: Singularity Of Soil Thermophiles and Thermophilic Extracellu...mentioning
confidence: 72%
See 1 more Smart Citation
“…It is important to note that the pioneering work [ 19 ] and some subsequent studies [ 43 , 45 ] included samples from soils exposed to hot temperatures and others from cold environments. Additional studies have shown significant roles of thermophiles at higher latitudes [ 16 , 17 , 49 , 50 , 51 , 52 ], corroborating that soil thermophiles can also show significant environmental activity in relatively cold climate zones.…”
Section: Singularity Of Soil Thermophiles and Thermophilic Extracellu...mentioning
confidence: 72%
“…The decomposition by thermophiles of oily food residues in soils has also been confirmed [ 49 ]. Thus, soil thermophiles expand the time when and conditions under which bioremediation could be carried out in soils [ 17 , 48 , 49 , 50 , 51 , 52 ], including periods of high temperature and drought in upper soil layers.…”
Section: Organic Matter Decompositionmentioning
confidence: 99%
“…Apart from deep-sea sediments, thermophiles, mostly spore-forming Firmicutes , have been discovered in many cold and temperate systems ( DePoy and King, 2023 ). Our findings of metabolically active thermophilic spores at temperatures below their growth range challenge the notion that many thermophiles can be inactive in mesothermic environments and simply maintained by a continuous input from geothermal sources ( Marchant et al, 2008 ; Zeigler, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we explored what ecological factors might be driving the lack of habitat generalists in our data set. First, we used a common method, beta nearest taxon index and Bray-Curtis-based Raup-Crick, to calculate contribution of different factors to community assembly in the 16S rRNA gene sequence data (44)(45)(46). We found that, across all sites, ecological drift was the strongest factor (30.5%), with homogenous dispersal (i.e., similar community structure caused by high dispersal rates) was the second strongest factor (25.5%) (Figure 5D).…”
Section: Habitat Specialization and Community Assembly Factorsmentioning
confidence: 99%